Psychopathology of Brain Frontal Lobe Tumors : When the Neurosurgery Meets Psychiatry - Domenico, Chirchiglia; Pasquale, Chirchiglia; Luca, Gallelli, (Journal of Spine and Neuroscience, 2017)
Brain tumors occur when abnormal cells form within the brain.There are two main types of tumors: malignant and benign tumors. Then, tumors can be divided into primary that start within the brain, and secondary tumors that have spread from somewhere else, known as brain metastasis tumors. Secondary brain tumors occur in approximately 15 % of cancer patients with about half of metastases coming from lung cancer. Primary brain tumors occur in around 250,000 people a year globally, making up less than 2% of whole body tumors. According to American Brain Tumor Association the most common types of primary tumors are gliomas, representing 74,6 % of all malignant tumors and meningiomas ( 36,6% ) while more affected region is frontal lobe, about 22 % . Particularly, prefrontal cortex ( PFC ), the anterior part of the frontal lobe that is highly developed in humans plays a role in the regulation of personality, emotional, and behavioral functioning, leading to serious cognitive impairments 1. These are the psychological signs of frontal lobe tumors, in addition to other functions such as the expressive language of Broca's area or those relating to voluntary movement, linked to frontal cortical motor areas. It relates to the so-called higher nervous functions, concerning the life of relationship and communication. The PFC physiology explains the psychological mechanisms of its associated functions: connections with the limbic cortex, thalamus, hypothalamus, basal ganglia and other subcortical areas.The regions of the PFC at the base of the psychophysiological mechanisms involved are basically the dorso-lateral, the ventro-medial, the orbito-frontal establishing contacts primarily with limbic structures, such as the cingulate gyrus, hippocampus, amygdala.
Keywords: pseudo-depression syndrome; pathy; lethargy